Foot reflexology therapy for non-specific low back pain condition : a protocol for a randomized controlled trial - Nor Dalila Marican,; Rozita Hod,; Nadiah Wan-Arfah,; Azmi Hassan, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction Non-specific low back pain is one of the most common physical ailments affecting millions of people worldwide. This condition constitutes a significant public health problem and was listed as a prevalent health complaint in most societies. Even though there are many anecdotal claims for reflexology in the treatment of various conditions such as a migraine, arthritis and multiple sclerosis, but very little clinical evidence exists for reflexology on the management of low back pain per se. This study aims to evaluate the effects of foot reflexology therapy as an adjunctive treatment to the Malaysian low back pain standard care in relieving pain and promoting health-related quality of life among people with non-specific low back pain. Methods This is a parallel randomized controlled trial with pre and post-treatment study design. The study setting for the intervention located at Penawar Reflexology Center, Kuala Terengganu, Malaysia. A total of 100 participants with non-specific low back pain will be allocated to one of two groups, using a randomization computer program of Research Randomizer. The control group will receive low back pain standard care, while the intervention group will receive standard care plus eight sessions of foot reflexology therapy. The pain intensity and health-related quality of life scores will be measured using Visual Analogue Scale and Euro-quality of life scale respectively in both groups. The study was approved by the Human Research Ethics Committee of University Sultan Zainal Abidin (UHREC/2016/2/011). The study protocol was registered at ClinicalTrials.gov, with the ID number of NCT02887430. Measurements Outcome measures will be undertaken at pre-intervention (week 1), post-intervention (week 6) and follow-up (week 10). Conclusions This will be the first trial to compare the foot reflexology therapy with control group among people who medically diagnosed with non-specific low back pain in Malaysia. The result of this study will contribute to better management of this population, especially for Malaysia healthcare setting.